EFFECT OF CULTIVATION RATE AND NITROGEN - 137 STRAIN ON LEAF LEVEL CHANGES (British Journal of Global Ecology and Sustainable Development, 2024)
In the article, the leaf surface of different soybean varieties changed depending on their biological characteristics. Planting rates (70, 80, 90 kg/ha) were increased, and the number of leaves per plant decreased when planted with Nitragin-137 strain.1 hectareit is stated that the total leaf level has increased.